2019
DOI: 10.1158/1078-0432.ccr-18-1574
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Kinases Identified by Genomic Analyses of Sporadic Microsatellite Instability–High Colorectal Cancers

Abstract: Purpose: Colorectal cancers with microsatellite instabilityhigh (MSI-H) status, due to mismatch repair deficiency, are associated with poor patient outcomes after relapse. We aimed to identify novel therapeutic targets for them.Experimental Design: We performed MSI analyses of over 2,800 surgically resected colorectal tumors obtained from consecutive patients treated in Japan from 1998 through June 2016. Whole-exome sequencing, transcriptome sequencing, and methylation analyses were performed on 149 of 162 tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
60
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 44 publications
14
60
2
1
Order By: Relevance
“…In line with the data reported by Cocco and colleagues (5), Sato and colleagues analyzed nearly 3,000 colorectal cancer cases from Japan and described remarkably similar results, with tumors harboring fusions in kinase genes being enriched in sporadic MSI-H, MLH1p, and RAS/BRAF wild-type colorectal cancer cases (6). Fifty-five percent of patients with sporadic colorectal cancer with MMR deficiency, MLH1p, and lack of mutations in the RAS/BRAF pathway harbored fusion genes.…”
supporting
confidence: 75%
“…In line with the data reported by Cocco and colleagues (5), Sato and colleagues analyzed nearly 3,000 colorectal cancer cases from Japan and described remarkably similar results, with tumors harboring fusions in kinase genes being enriched in sporadic MSI-H, MLH1p, and RAS/BRAF wild-type colorectal cancer cases (6). Fifty-five percent of patients with sporadic colorectal cancer with MMR deficiency, MLH1p, and lack of mutations in the RAS/BRAF pathway harbored fusion genes.…”
supporting
confidence: 75%
“…Because the MSI status of cancer cells is used as a response predictor for immune checkpoint inhibitors, we designed DNA capture probes for 10 microsatellite regions including those designated in the Bethesda panel . Moreover, additional probes were included in the TOP DNA panel V2 to interrogate 500 microsatellite loci that were commonly altered in our WES analysis of high‐MSI colorectal cancer . To detect MMR‐deficient tumors, MSIsensor scores were calculated using the TOP DNA sequence data.…”
Section: Resultsmentioning
confidence: 99%
“…Marker, 1-kb DNA ladder; NC, negative control the Bethesda panel 40. Moreover, additional probes were included in the TOP DNA panel V2 to interrogate 500 microsatellite loci that were commonly altered in our WES analysis of high-MSI colorectal cancer 41. To detect MMR-deficient tumors, MSIsensor scores 42 were calculated using the TOP DNA sequence data.…”
mentioning
confidence: 99%
“…The data used in this study were obtained and described in the previous report . Patients with CRC gave written informed consent prior to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…CIMP is found in various types of cancers, and was reported to be a clinically distinct subset in CRC . Using the recently enriched transcriptome database and our recently published data from genome‐wide methylation analysis of MSI‐H CRC, here we analyzed the methylation status of div‐CGI and found that div‐CGI were less methylated compared with CGI within unidirectional promoters (uni‐CGI) in normal colon cells as well as in CRC cells. These results provide important insights to understand the aberrant promoter CGI methylation in cancer cells.…”
Section: Introductionmentioning
confidence: 99%